2023
DOI: 10.3390/vaccines11020223
|View full text |Cite
|
Sign up to set email alerts
|

Communicating with Patients about COVID-19 Vaccination: A Qualitative Study on Vaccinators in Tuscany Region, Italy

Abstract: The rapid development of the vaccine and the infodemia have challenged communication about COVID-19 vaccines. This study aims to characterize—through the experience of vaccinators—the challenges faced during COVID-19 vaccination consultations and the communication strategies adopted. A qualitative study was conducted on COVID-19 vaccinators in Tuscany, Italy. Face-to-face interviews were conducted and examined by thematic analysis. In total, 30 vaccinators were interviewed. Four main themes emerged. The first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In addition to necessary accommodations, structural change, and public health programs, a major factor that can impact patients who are vaccine hesitant is improved communication with physicians and medical professionals. Previous studies have also suggested that receiving information from healthcare workers help patients to develop vaccine awareness, thus minimizing misinformation, and that concerns are magnified due to a lack of clear communication [ 20 , 30 ]. When discussing vaccines with hesitant patients, physicians engaging in an open dialogue in which patients can express their concerns without judgment tend to be more effective in damping those concerns and discussing vaccines in a more positive manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to necessary accommodations, structural change, and public health programs, a major factor that can impact patients who are vaccine hesitant is improved communication with physicians and medical professionals. Previous studies have also suggested that receiving information from healthcare workers help patients to develop vaccine awareness, thus minimizing misinformation, and that concerns are magnified due to a lack of clear communication [ 20 , 30 ]. When discussing vaccines with hesitant patients, physicians engaging in an open dialogue in which patients can express their concerns without judgment tend to be more effective in damping those concerns and discussing vaccines in a more positive manner.…”
Section: Discussionmentioning
confidence: 99%
“…The current literature emphasizes the critical importance of promoting vaccine access, uptake, and confidence in ND communities, especially through use of healthcare professionals as they are often the main source that families receive information about vaccines from [ 20 , 21 ]. However, there is a need for research that focuses on communication strategies supported by healthcare professionals with specific focus on promoting vaccine confidence in ND communities.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, “over-zealous” national governments discontinued the use of a specific vaccine against World Health Organization recommendations, undermining confidence in its safety ( 6 ). This lack of coordinated, effective messaging around COVID vaccination compounded an existing dearth of trust in public institutions and served to further hinder demand creation for the vaccine ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is true across the world- in a large, qualitative study on vaccine demand creation among pregnant women in Kenya, several participants recalled a persuasive radio advertisement featuring a man paralyzed by polio who wished he had been vaccinated as a child ( 18 ). At the provider level, where directly addressing misinformation can increase hesitancy, active and empathetic listening is a key avenue for reaching vaccine hesitant individuals and their children ( 7 , 19 , 20 ). While social media companies have responded to misinformation by increasing fact-checking efforts and removing disinformation, these are often “too little, too late” ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, since medical universities are forges of future healthcare workers who should be able to communicate with their patients about vaccination, vaccine hesitancy, and vaccine conspiracy theories [49][50][51], this study, therefore, seeks to explore future doctors' attitudes towards anti-vaccine conspiracy theories. Although only recently several studies on Polish medical students' COVID-19 vaccine hesitancy have been conducted [52][53][54], they often focus on students' knowledge and willingness to get vaccinated.…”
Section: Introductionmentioning
confidence: 99%